The trauma of gender : a feminist theory of the English novel - Moglen, Helene, 1936-2018 (University of California Press, 2001)
Helene Moglen offers a revisionary feminist argument about the origins, cultural function, and formal structure of the English novel. While most critics and historians have associated the novel's emergence and development with the burgeoning of capitalism and the rise of the middle classes, Moglen contends that the novel princi- pally came into being in order to manage the social and psychological strains of the modern sex-gender system.